From punishment to dialogue: the practice of school reconciliation services - E.G. Pastukhova (Социальная психология и общество)
Context and relevance. School plays a crucial role in the socialization process, providing students with opportunities to develop their personalities and learn to navigate challenges. Conflicts that arise within the educational environment – an inevitable part of social interaction – are viewed by social psychology as valuable experiences for learning constructive ways to resolve disputes. One effective means of supporting this development is the implementation of a restorative approach through school-based reconciliation services. Objective. To examine the practical implementation of the restorative approach as a key aspect of socio-psychological work in schools. Research questions. 1) What forms the foundation of the restorative approach, according to leading restorative programs? 2) What mechanisms are employed in the implementation of these restorative programs? 3) What types of conflicts does the School Reconciliation Service engage in resolving? Methods and materials. 1) A total of 2676 checklists detailing rehabilitation programs implemented in Moscow between 2022 and 2025 were analyzed. The data were examined using frequency analysis and presented through qualitative content analysis. 2) Eleven in-depth interviews were conducted with leaders of restorative programs. The collected data were processed using methods of mathematical analysis. Results. The analysis yielded data on the distribution of types of restorative programs, the nature of the issues addressed, and the sources of program initiation. The thematic focus of conflict situations was identified, reflecting the current state of the school environment. Key characteristics and mechanisms of the restorative approach were also outlined based on the perspectives of leading restorative programs. Conclusions. The restorative approach in schools presents a humanistic alternative to traditional punitive practices, placing emphasis on dialogue, empathy, and mutual understanding. It is applied both in resolving interpersonal conflicts and in fostering a more positive psychological climate within the school community. Through participation in restorative programs, individuals develop constructive communication skills and learn to take responsibility for their actions. The primary causes of conflict include issues related to personal honor, property disputes, interethnic tensions, group dynamics, and cyberbullying.